2014
DOI: 10.1093/ofid/ofu021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Immunodeficiency Virus on the Severity of Buruli Ulcer Disease: Results of a Retrospective Study in Cameroon

Abstract: The impact of human immunodeficiency virus (HIV) infection on Buruli ulcer (BU) severity and prevalence remains unclear. This study shows that patients who are HIV positive are at risk for BU. Notably, HIV-induced immunosuppression seems to have an impact on BU clinical presentation and disease evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 23 publications
4
74
0
1
Order By: Relevance
“…A retrospective study conducted in Cameroon revealed that human immunodeficiency virus (HIV) infection may affect the clinical presentation and severity of BU disease with a reported increased incidence of multiple, larger, and ulcerated BU lesions. [16][17][18] Data available on the absorption of antituberculosis medications in tuberculosis (TB)/HIV coinfection compared with HIV-negative patients showed conflicting results. 19,20 Therefore, whether antimycobacterial combination treatment is less efficacious in persons with HIV infection is unknown and needs to be systematically studied.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study conducted in Cameroon revealed that human immunodeficiency virus (HIV) infection may affect the clinical presentation and severity of BU disease with a reported increased incidence of multiple, larger, and ulcerated BU lesions. [16][17][18] Data available on the absorption of antituberculosis medications in tuberculosis (TB)/HIV coinfection compared with HIV-negative patients showed conflicting results. 19,20 Therefore, whether antimycobacterial combination treatment is less efficacious in persons with HIV infection is unknown and needs to be systematically studied.…”
Section: Introductionmentioning
confidence: 99%
“…77 Two recent case-control studies carried out in Benin and Ghana reported a significant effect of HIV infection on the severity of M. ulcerans infections and provided evidence suggestive of a higher HIV incidence in patients with BU compared with the general population. 102,103 Furthermore, observations in case studies indicate a more severe disease in HIV patients.…”
Section: Hiv Statusmentioning
confidence: 99%
“…The latest is poorly understood, but well documented [3]. IRIS occurs in the setting of Anti-retroviral treatment (ART) initiation and it is considered as a deregulated immunologic response to a previously existing pathogen such as mycobacterium ulcerans in Buruli ulcer.…”
Section: Editorialmentioning
confidence: 99%